Assessing health risk due to exposure to arsenic in drinking water in Hanam Province, Vietnam - Tung Bui Huy; Tran Thi Tuyet Hanh; Johnston, R.; Hung Nguyen-Viet (MDPI, 2014)
We assessed health risks related to Arsenic (As) in contaminated drinking water in Hanam, applying the Australian Environmental Health Risk Assessment Framework, which promotes stakeholder involvement in risk assessments. As concentrations in 300 tube-well water samples, before and after filtration, were analyzed and the water consumption levels in 150 households were estimated. Skin cancer risk was characterized using Cancer Slope Factor index and lifetime average daily dose with a probabilistic approach. The results showed that arsenic concentrations in tube-well water ranged from 8–579 ppb (mean 301 ppb) before filtration and current sand filters used by the households did not meet the standard for As removal. Arsenic daily consumption of 40% of the adults exceeded the level of TDI (Tolerable Daily Intake) at 1 µg/kg/day. The average skin cancer risk in adults due to consuming filtered tube-well water for drinking purpose were 25.3 × 10−5 (using only well water) and 7.6 × 10−5 (using both well and rain water). The skin cancer risk would be 11.5 times higher if the water was not filtered. Improvement of filtration measures or the replacement of the current drinking water sources to minimize the health risks to the local population is urgently needed.